Four new species of Coelinius (Hymenoptera: Braconidae: Alysiinae) from the neotropical region - Souza-Gessner, Carolina Da Silva; de Almeida, Luis Felipe Ventura; Penteado-Dias, Angélica Maria (Zootaxa, 2019)
The genus Coelinius (Hymenoptera: Braconidae: Alysiinae) is reported for the first time from Brazil and the Neotropical region. The genus occurs in southeastern Brazil, in the states of Minas Gerais, Rio de Janeiro and São Paulo. Four new species of Coelinius are described and illustrated: C. canastra sp. nov, C. itamonte sp. nov., C. kali sp. nov. and C. lux sp. nov.